2022
DOI: 10.1088/1755-1315/985/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Microclimate Dynamics In Sweet Corn Intercropping with Various Legumes

Abstract: Sweet corn is generally grown in monoculture with wide spacing because it is easier to do but less effective and efficient in using resources, which cause the microclimate around sweet corn to be not optimal for its growth. Intercropping can improve the microclimate due to the presence of intercrops between the sweet corn. The type of intercrops affect the microclimate around sweet corn. This research aims to determine the effect of various legumes on the abiotic environment and find the legumes that can creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Soybean yield is highly dependent on the number of pods produced, which is an indicator of the plant's health. The NPP results soybean varieties Setiawan et al, (2023), highlighting the significance of this finding. Studies by Pedersen & Lauer, (2004) showed that adjusting sowing dates can increase pod and seed quantity, and Adetokunbo et al, (2019) also highlighted the importance of pods and seeds per plant in soybean seed production.…”
Section: Yield Associated Traitsmentioning
confidence: 61%
“…Soybean yield is highly dependent on the number of pods produced, which is an indicator of the plant's health. The NPP results soybean varieties Setiawan et al, (2023), highlighting the significance of this finding. Studies by Pedersen & Lauer, (2004) showed that adjusting sowing dates can increase pod and seed quantity, and Adetokunbo et al, (2019) also highlighted the importance of pods and seeds per plant in soybean seed production.…”
Section: Yield Associated Traitsmentioning
confidence: 61%
“…Corn-soybean intercropping is one of the main cereal-legume intercropping systems used, and it is distributed throughout most of the world [22], including Africa [23], America [24], Asia [25], Australia [26], and Europe [27]. The effects of the intercropping system on crop yields, land use efficiency, and nitrogen fertilizer use on grain or silage corn in corn-soybean intercropping systems have been reported [22,[28][29][30]; however, studies on the intercropping of sweet corn and soybean are limited [31][32][33].…”
Section: Introductionmentioning
confidence: 99%